Specialized Proresolving Lipid Mediators: A Potential Therapeutic Target for Atherosclerosis - Salazar, Juan; Pirela, Daniela; Nava, Manuel; Castro, Ana; Angarita, Lissé; Parra, Heliana; Durán-Agüero, Samuel; Rojas-Gómez, Diana Marcela; Galbán, Néstor; Añez, Roberto; Chacín, Maricarmen; Diaz, Andrea; et al. (International journal of molecular sciences, 2022)
Cardiovascular disease (CVD) is a global public health issue due to its high morbidity, mortality, and economic impact. The implementation of innovative therapeutic alternatives for CVD is urgently required. Specialized proresolving lipid mediators (SPMs) are bioactive compounds derived from ω-3 and ω-6 fatty acids, integrated into four families: Lipoxins, Resolvins, Protectins, and Maresins. SPMs have generated interest in recent years due to their ability to promote the resolution of inflammation associated with the pathogeneses of numerous illnesses, particularly CVD. Several preclinical studies in animal models have evidenced their ability to decrease the progression of atherosclerosis, intimal hyperplasia, and reperfusion injury via diverse mechanisms. Large-scale clinical trials are required to determine the effects of SPMs in humans. This review integrates the currently available knowledge of the therapeutic impact of SPMs in CVD from preclinical and clinical studies, along with the implicated molecular pathways. In vitro results have been promising, and as such, SPMs could soon represent a new therapeutic alternative for CVD.
Keywords: Docosahexaenoic Acids; kardiovaskulární nemoci; ateroskleróza; Animals; Inflammation; Fatty Acids, Omega-3; omega-3 mastné kyseliny; mediátory zánětu; lidé; zánět; Atherosclerosis; zvířata; Inflammation Mediators; Cardiovascular Diseases; kyseliny dokosahexaenové; Humans